Pluralisme Dalam Perspektif Islam: Analisis Tafsir Madlu’i - Ramdan, Zamzam Muhamad; Aulia, Nurfadilah; Nisrina, Hana Fitri; Agustina, Revalina Nazwa; Putra, Daffa Jilbransyah; Sofyan, Muhammad Agil; Muhyi, Asep Abdul; Chodijah, Siti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the concept of religious pluralism from an Islamic perspective, focusing on its theological and social dimensions through a thematic interpretation (tafsir maudhu’i) of relevant Qur’anic verses. The research employs a qualitative method based on literature review, using content analysis of the Qur’an and scholarly works from both Islamic and Western thinkers on pluralism. The main theoretical framework is the theory of religious pluralism, which emphasizes the acknowledgment of belief diversity, as proposed by figures such as John Hick and critically examined by Islamic scholars. The findings indicate that pluralism in Islam does not imply the theological equality of all religions, but rather recognizes religious diversity as a social reality willed by God. The Qur’an promotes values of tolerance, justice, and coexistence within diversity. Thus, Islam supports the principle of pluralism in social and ethical terms, while maintaining the normative truth claim of its own teachings.